Effect of haemophilus influenza vaccination on admission for pneumonia and meningitis in Hospital USM - Idris, Siti Aisyah (2018)
Objective – To study the impact of implementation of Haemophilus influenzae b (Hib) vaccination on the total number of hospital admission for pneumonia and meningitis in Hospital Universiti Sains Malaysia from year 2000 up to 2017. Methods – retrospective study based on diagnosis recorded by Medical Records Unit Hospital USM from the patients’ discharge summaries. Patients included in this study are those within age of 3 to 60 months during admission and when the diagnosis was made and admitted for pneumonia and meningitis. Poisson regression was used to determine the association between number of admission before and after immunization. Results – Analyses showed that number of admission for pneumonia (RR = 3.5, 95% CI: 1.3, 13.6) and lengths of stay in days (RR = 2.7, 95% CI: 1.2, 7.2) significantly increased with the starting of Hib immunization. However, all models had poor goodness-of-fit (predicted count did not fit the data). Conclusions – Based on the analyses of the data, we cannot correlate between the implementation of Hib vaccination with current incidence of pneumonia and meningitis as there are many other factors that influence both the illness. In addition, there were many missing data as this is a retrospective study. Further studies are warranted.